A Proposed Strategy for Developing the Performance of the Faculties of Education in the Palestinian Universities by Using the Independent Cost Unit: A Case Study of Islamic University - Eyad A. Adjani; Noor Y. esleem; Anisa H. Eldohdar (University of Science and Technology, Yemen, 2020)
The study aimed at proposing a strategy for developing the performance of the Faculties of Education in the Palestinian universities by using the independent cost unit, through examining the actual performance of the Faculties of Education in the Palestinian universities. The content analysis method and the constructive method were used in this study based on two tools which were the content analysis card for the Executive Plan of the Faculty of Education for the years 2016-2017 / 2017-2018, and the Delphi method. The study results showed that the institutional performance of the Faculty of Education had a relative weight (68.3%) in the academic field, (64.3%) in the administrative field and (89.7%) in the financial field. Thus, the study recommended the Faculty of Education to adopt the strategy and provide appropriate conditions for its implementation.